Topography of Primary Molar Pulp Chamber Floor: A Scanning Electron Microscopy and Micro-Computed Tomography Analysis - Ana Victória Lopes Bandeira; Marina de Deus Moura de Lima; Cacilda Castelo Branco Lima; Marcoeli Silva de Moura; Altair Antoninha Del Bel Cury; Lucia de Fátima Almeida de Deus Moura (Association of Support to Oral Health Research (APESB), 2021)
Objective: To determine in vitro the frequency, shape, type, diameter, and patency of accessory canals in the primary molars pulp chamber floor. Material and Methods: Sixteen healthy primary molars were evaluated by micro-computed tomography and scanning electron microscopy. Descriptive analyses of the frequency, shape (round, oval, or irregular), type (blind, true, or hidden), patency and diameter of the accessory canals were performed. Results: Half of the teeth presented accessory canals, 62.5% of which were located in the upper molars and 37.5% in the lower molars. The most frequent shape was irregular. In three-dimensional analysis, blind accessory canals (12.5%) and with patency (18.7%) of the teeth were observed. The average accessory canal diameter was 51.97 µm (± 26.03 µm). Conclusion: Upper molars showed a higher frequency of accessory canals with larger diameters. The irregular shape was the most frequent. 18.7% of accessory channels showed patency.